Carboxylic Acid Production - Gunnar Lidén (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Carboxylic acids are truly central compounds in cellular metabolism. Carbon dioxide is captured from the atmosphere through formation of carboxylic groups and is also released, in part, by decarboxylation reactions. The reactivity of the carboxylic group with amino- or hydroxyl-groups enables the formation of peptide and ester bonds. The functionality of the carboxylic group is also of huge importance in our industrial world for a wide range of applications. The loosely bound hydrogen provides weak acid functionality, much desired for food industry applications in preservatives and flavour compounds. Citric acid is one of our oldest industrial fermentation products. The presence of two carboxylic groups, or a combination of one carboxylic group and another functional group, make the compounds interesting building blocks for polymer production. A number of carboxylic acids, including, e.g., lactic, succinic, 3-hydroxypropionic and itaconic acids, have been identified and recognized as suitable platform chemicals for a foreseen growing carbohydrate based economy. Economic margins are, however, tight when competing with petroleum based production, and production strains, fermentation technology and-not least-downstream processing, all need to be improved to enable viable commercial production. This Special issue will cover current developments within this exciting field. Topics will include: Fermentation physiology of natural carboxylic acid producers; screening and isolation of novel producers; metabolic engineering for improving intrinsic carboxylic acid production; metabolic engineering for expanding product range to non-endogenous carboxylic acids; production from lignocellulosic derived sugars or by-product streams; downstream processing for recovery of carboxylic acids; bioprocess design-including continuous processes and integration. All production organisms-fungi, yeasts, bacteria-are welcome.